Evaluation of periphyton utilization by oreochromis mossambicus and clarias gariepinus in aqua dams in Limpopo Province, South Africa - Hlongwane, Khathutshelo Cathrine (My University, 2025)
The high cost of fish feed in developing countries makes it imperative to develop aquaculture technologies that can produce natural food in production systems without increasing input costs. Periphyton-based aquaculture promotes the growth of periphyton on submerged substrates in water, which serves as a preferred natural food forvherbivorous and omnivorous fish such as tilapia and African catfish. Tilapia and African catfish are one of the most widely cultured species in Africa. In this study, the utilisation of periphyton by Oreochromis mossambicus (Mozambique tilapia) and Clarias gariepinus (African catfish) in aqua dams with net, plastic and stone substrates was investigated. The study aimed to reduce the cost of fish feed in rural aquaculture by enhancing the utilisation of periphyton by Mozambique tilapia and African catfish in aqua dams. Locally available materials were used as substrates for growing periphyton in the aqua dams. Periphyton dynamics in periphyton-based aquaculture are influenced by several factors thus, it was important to first determine the composition of periphyton in aqua dams before stocking the fish. The growth of periphyton on substrates in water also enhances the growth of bioseston in the water column. Therefore, the effect of substrates on periphyton and bioseston was explored simultaneously to fully understand the periphyton dynamics in aqua dams in summer and winter. Net, plastic and stone were deployed separately in the nine aqua dams in a completely randomised design in winter and summer. The experiment ran for 21 days in each season. The periphyton and bioseston were categorised as periphytic algae, metazoans, ciliates, protists, and aquatic invertebrates to easily distinguish the periphyton and bioseston communities. Periphytic algae was the most abundant category on all substrates in both winter and summer probably because they have adaptive features that enable them to thrive in various environments. The composition of periphyton and bioseston in the aqua dam with net, plastic and stone during winter and summer showed that substrate, season and grazing played a significant role. The composition and abundance of periphyton and bioseston were significantly higher (P < 0.05, ANOSIM) on the net and lowest on the stone substrate in both winter and summer. The net substrate also had the highest periphyton biomass (in terms of dry matter) while the stone substrate had the lowest in both summer and winter. This was because the texture, surface area and position of the substrate influenced the abundance and composition of periphyton and bioseston in aqua dams. Summer had higher periphyton and bioseston abundance than winter because the temperature was optimal for their growth Network analysis was later used to determine the pattern of the community structure of periphyton and bioseston in aqua dams in winter and summer and showed a weak community structure. This was caused by low genera diversity due to the similarities in water quality parameters and the high abundance of periphytic algae in both seasons. This indicated that the genera on one substrate were most likely to be found on another substrate despite the season. Subsequent to understanding factors affecting periphyton and bioseston composition in aqua dams with substrates, fish were then stocked into the aqua dams. To determine the utilisation of periphyton and bioseston by the fish in the aqua dams, three feeding regimes were designed. In the first feeding regime, the fish were fed every day (twice a day) and this was designated: N100, P100, and S100. The first feeding regime (N100, P100 and S100) represented the control because fish are normally fed twice every day at fish farms. In the second feeding regime, the fish were fed commercial pellets every other day (twice a day), and this was designated: N50, P50, and S50. In the third feeding regime, the fish were fed every third day (still twice a day), and this was designated N33, P33, and S33. Mozambique tilapia fingerlings (5.44 ± 0.81 g, mean ± SE) were stocked into the aqua dams with net, plastic and stone substrates in a completely randomised design for six weeks. Unexpectedly, specific growth rate and condition factor were significantly (P < 0.05, MANOVA) higher in aqua dams with plastic substrates. In prior experiments in aqua dams without fish, the net substrate had the highest periphyton biomass. However, the net substrate did not result in the highest fish growth rate (Chapter 4).This was probably because periphyton and bioseston in aqua dams with plastic substrate were accessible and of high quality. This shows that the periphytic algae, metazoans, ciliates, protists, and aquatic invertebrates provided sufficient protein, energy, and lipids to compensate for the nutritional value of the deprived commercial pellets. Furthermore, it was concluded that commercial pellets can be reduced by 50 to 67 % in aqua dams with periphyton substrates. Mozambique tilapia of three different size groups (2.62 ± 0.01 g, 5.08 ± 0.02 g and 25.24 ± 0.29 g; mean ± SE) were further observed for 24 hours to determine their feeding preferences between periphyton and bioseston in fibreglass tanks. The results showed that Mozambique tilapia did not show a preference between periphyton and bioseston, the fish was not actively selecting any food items. This was because Mozambique tilapia can nip and scrap periphyton from substrates and also filter feed on bioseston using gill rakers. Furthermore, the most abundant and dominant periphyton and bioseston in the fibreglass tanks were also abundant in the stomachs of all tilapia size groups. This indicates that Mozambique tilapia was ingesting the most abundant periphyton and bioseston. Diatoms were also abundant and dominant in the stomachs of all tilapia size groups but also abundant in the faecal matter. This indicates that diatoms were not digested, probably because tilapia lacked silica-reinforced teeth to break the diatom’s cell wall. The utilisation of periphyton and bioseston by African catfish was also explored. The same experiments and feeding regimes mentioned above were adopted to determine if African catfish is a good candidate for periphyton-based aquaculture. African catfish (200.2 ± 22.74 g, mean ± SD) were also stocked in the aqua dams in a complete randomised design for six weeks. The results showed that in aqua dams with net and plastic substrates, the highest specific growth rate was recorded in N100 and P100. However, in aqua dams with stone substrates, the highest specific growth rate was recorded in S33. Both N100 and P100 represented the control where the African catfish were fed commercial pellets twice, every day. The fish in S33 aqua dams were fed commercial pellets every third day. This indicates that catfish in S33 were able to utilise periphyton on stone substrates since the growth rate was comparable with the controls. This was attributed to its large lower jaw extensibility which enabled it to scoop periphyton from the stone substrates. This suggests that stone substrates can used in aqua dams stocked with African catfish to reduce commercial pellet input by 67 %. In the prior experiments, the stone substrate had the least periphyton composition and biomass, but this suggests that its nutritional value was sufficient to compensate for the nutritional value of the deprived commercial pellets. The results also showed that each substrate significantly influenced the growth performance of African catfish differently. However, there was no distinct pattern to conclude where the fish grew faster between the net, plastic and stone substrates. This was probably because the net substrate had the highest periphyton abundance and plastic had more genera of animal origin while the periphyton on the stone was more accessible to African catfish to easily scoop. The results also showed that African catfish selectively fed on insects, Chironomidae larvae, and Cladocera. Furthermore, insects and Chironomidae were important food items in the diet of African catfish across the different substrates. This was because African catfish have predatory behaviour and commonly prefer food items of animal origin. However, diatoms, Microcystis sp. and Difflugia sp. dominated the faecal matter indicating that African catfish lack gastric juices and silica-reinforced teeth to digest them. Lastly, an aquaculture recirculating system was designed to determine the impact of periphyton-based biofilters on water quality parameters. To determine the efficacy of a periphyton-based biofilter in maintaining optimal water quality parameters for tilapia culture, Mozambique tilapia (5.00 ± 1.14 g, mean ± SD) was stocked in the tanks. Net, plastic and stone were used as biofilters in duplicate in a completely randomised design. Nitrifying bacteria were not seeded but the periphyton was allowed to form naturally for three weeks before commencement of the experiment. The water quality parameters were monitored daily for three weeks to determine the overall performance of the periphyton-based biofilters. The water quality parameters were also determined for a period of 24 hrs at four-hour intervals (once every week) to monitor the diurnal dynamics in the periphyton-biofilters. The results showed the diurnal mean levels mirrored the average water quality parameters across the periphyton-biofilters over the period of three weeks. Nitrate levels significantly varied (P < 0.05) between the periphyton biofilters, net periphyton-biofilter registered the highest nitrate levels and stone registered the lowest levels. This indicates that nitrification effectively occurred in the net periphyton-biofilter contributing to the accumulation of nitrate. However, the accumulated nitrate was within the optimum range for farming tilapia. Nitrite was significantly higher (P < 0.05) in the plastic periphyton-biofilter than in net and stone periphyton-biofilter. High nitrite levels probably indicate there was imbalanced nitrite-oxidising microbial activity which led to nitrite accumulation in the plastic periphyton-biofilter. Nitrite can be toxic to tilapia when it's above 1.0 mg/l. However, the recorded level of nitrite was within the optimum range for farming tilapia, below 0.5 mg/l. The stone periphyton-biofilter registered the highest (P < 0.05) ammonia levels and plastic registered the lowest levels. The accumulation of ammonia indicates that nitrification was not effective and inadequate in the stone periphyton-biofilter. Even though ammonia was highest in the stone periphyton-biofilter, it was still within the farming range for tilapia. The total phosphate recorded in the periphyton-biofilter was slightly higher than that recorded in the aqua dams. This suggests that the periphyton community on the plastic substrate was not dominated by algae that can take up phosphate in the form of inorganic phosphorus. Dissolved oxygen and pH levels were optimum for tilapia and water purification processes in all the biofilters. The net was an effective periphyton-based biofilter since it was able to maintain the toxic ammonia and nitrite at minimal levels. This study recommends using periphyton substrate in aquaculture to reduce feed costs. Durable plastic substrates can be used in aqua dams stocked with tilapia to reduce commercial pellet input by 50 to 67 %. Stone substrates can used in aqua dams stocked with African catfish to reduce commercial pellet input by 67 %. Nonetheless, the use of other substrates needs to be explored. Furthermore, the study recommends using periphyton-based biofilters to maintain the water quality parameters optimum for fish production in a recirculating system. In this study, the net was the most efficient periphyton-based biofilter and we recommend that the net periphyton-biofilter be tested in a large-scale production system. Further experiments should be conducted to determine the feeding preference of African catfish between periphyton and bioseston.
Thesis (Ph. D. (Aquaculture)) -- University of Limpopo, 2025
Keywords: Pheriphyton; Oreochromis mossambicus; Clarias gariepinus; Aqua dams; Limpopo Province; Evaluation; Periphyton; Mozambique tilapia; Clarias gariepinus